The Effectiveness of Virtual Learning Environments in Developing Digital Marketing Skills - Trissetianto, Andri Catur; Ali, Hapzi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This study examines the effectiveness of Virtual Learning Environments (VLEs) in fostering digital marketing skills among higher education students. Employing a mixed-methods approach, the research integrates quantitative data from pre- and post-tests with qualitative insights obtained through interviews and focus groups. The findings indicate a significant improvement in students' competencies, particularly in content creation, social media strategy, and data analysis. Key features—such as real-time simulations, gamification, and collaborative tools—played a vital role in enhancing learner engagement and practical application. Students also appreciated the flexibility of asynchronous learning and the opportunity to experience real-world scenarios. However, issues such as digital fatigue, motivational decline, and limited access in remote areas were identified as challenges. The study concludes that VLEs can serve as effective platforms for skill-based learning if supported by sound instructional design, consistent teaching presence, and adequate technological infrastructure. These results contribute to the broader discourse on digital education and provide actionable recommendations for improving online marketing instruction.